CaMKK2 facilitates Golgi-associated vesicle trafficking to sustain cancer cell proliferation - Stewart, L; Gerner, L; Rettel, M; Stein, F; Burrows, J; Mills, IAN; Evergren, E (Springer Nature, 2021)
Calcium/calmodulin-dependent protein kinase kinase 2 (CaMKK2) regulates cell and whole-body metabolism and supports tumorigenesis. The cellular impacts of perturbing CAMKK2 expression are, however, not yet fully characterised. By knocking down CAMKK2 levels, we have identified a number of significant subcellular changes indicative of perturbations in vesicle trafficking within the endomembrane compartment. To determine how they might contribute to effects on cell proliferation, we have used proteomics to identify Gemin4 as a direct interactor, capable of binding CAMKK2 and COPI subunits. Prompted by this, we confirmed that CAMKK2 knockdown leads to concomitant and significant reductions in δ-COP protein. Using imaging, we show that CAMKK2 knockdown leads to Golgi expansion, the induction of ER stress, abortive autophagy and impaired lysosomal acidification. All are phenotypes of COPI depletion. Based on our findings, we hypothesise that CAMKK2 sustains cell proliferation in large part through effects on organelle integrity and membrane trafficking.